Molecular Mechanism Study on Stereo-Selectivity of α or β Hydroxysteroid Dehydrogenases - Miaomiao Gao; Kaili Nie; Meng Qin; Haijun Xu; Fang Wang; Luo Liu (Crystals, 2021)
Hydroxysteroid dehydrogenases (HSDHs) are from two superfamilies of short-chain dehydrogenase (SDR) and aldo–keto reductase (AKR). The HSDHs were summarized and classified according to their structural and functional differences. A typical pair of enzymes, 7α–hydroxysteroid dehydrogenase (7α–HSDH) and 7β–hydroxysteroid dehydrogenase (7β–HSDH), have been reported before. Molecular docking of 7-keto–lithocholic acid(7–KLA) to the binary of 7β–HSDH and nicotinamide adenine dinucleotide phosphate (NADP+) was realized via YASARA, and a possible binding model of 7β–HSDH and 7–KLA was obtained. The α side of 7–KLA towards NADP+ in 7β–HSDH, while the β side of 7–KLA towards nicotinamide adenine dinucleotide (NAD+) in 7α–HSDH, made the orientations of C7–OH different in products. The interaction between Ser193 and pyrophosphate of NAD(P)+ [Ser193–OG⋯3.11Å⋯O1N–PN] caused the upturning of PN–phosphate group, which formed a barrier with the side chain of His95 to make 7–KLA only able to bind to 7β–HSDH with α side towards nicotinamide of NADP+. A possible interaction of Tyr253 and C24 of 7–KLA may contribute to the formation of substrate binding orientation in 7β–HSDH. The results of sequence alignment showed the conservation of His95, Ser193, and Tyr253 in 7β–HSDHs, exhibiting a significant difference to 7α–HSDHs. The molecular docking of other two enzymes, 17β–HSDH from the SDR superfamily and 3(17)α–HSDH from the AKR superfamily, has furtherly verified that the stereospecificity of HSDHs was related to the substrate binding orientation.